(untitled) (Third Sector Social Economic Review, 2017)
Orhan Kemal is a prominent writer who actively contributed emergence of the working class as a popular topic in Turkish literature of novels and stories. His observations on the process of the shift of people from peasantry to the workers and his literary fiction built upon these observations took place mainly on the issues of the formation of working class in Turkey in the years of the birth of industrialization and urbanization in Turkey. In this study, these observations and propositions of Orhan Kemal will be held in a sociological analysis. Furthermore, considering Orhan Kemal himself had been a worker, it is going to be brought up in the frame of this work whether Orhan Kemal is an organic intellectual. In terms of the analysis of the labour aspect of Turkish modernization, the literature of Orhan Kemal went through number of ways of analyses in this article.